2022
DOI: 10.1111/geb.13473
|View full text |Cite
|
Sign up to set email alerts
|

The conservation impacts of ecological disturbance: Time‐bound estimates of population loss and recovery for fauna affected by the 2019–2020 Australian megafires

Abstract: Aim: After environmental disasters, species with large population losses may need urgent protection to prevent extinction and support recovery. Following the 2019-2020 Australian megafires, we estimated population losses and recovery in fire-affected fauna, to inform conservation status assessments and management.Location: Temperate and subtropical Australia. Time period: 2019-2030 and beyond.Major taxa: Australian terrestrial and freshwater vertebrates; one invertebrate group. Methods:From > 1,050 fire-affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
54
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 60 publications
(64 citation statements)
references
References 96 publications
0
54
2
Order By: Relevance
“…Directly documenting changes in density after fires of variable severity improves our understanding of population processes in relation to fire; a common disturbance event in Australian forests and one that is predicted to increase in frequency and severity with climate change (Bowman et al., 2017; Clarke & Evans, 2019). At present, direct responses of forest species to the recent mega‐fires are poorly known and rapid post‐fire assessments have relied substantially on expert opinion (Legge et al, 2022) or extrapolation based on fire extent without considering severity (Ward et al., 2020). Expert elicitation for the koala suggested the most plausible population loss to severe fire was 77% 1 week after fire and 63% after 10 years (with uncertainty increasing with time since fire), making the koala one of the most sensitive species to severe fire (Legge et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Directly documenting changes in density after fires of variable severity improves our understanding of population processes in relation to fire; a common disturbance event in Australian forests and one that is predicted to increase in frequency and severity with climate change (Bowman et al., 2017; Clarke & Evans, 2019). At present, direct responses of forest species to the recent mega‐fires are poorly known and rapid post‐fire assessments have relied substantially on expert opinion (Legge et al, 2022) or extrapolation based on fire extent without considering severity (Ward et al., 2020). Expert elicitation for the koala suggested the most plausible population loss to severe fire was 77% 1 week after fire and 63% after 10 years (with uncertainty increasing with time since fire), making the koala one of the most sensitive species to severe fire (Legge et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…At present, direct responses of forest species to the recent mega‐fires are poorly known and rapid post‐fire assessments have relied substantially on expert opinion (Legge et al, 2022) or extrapolation based on fire extent without considering severity (Ward et al., 2020). Expert elicitation for the koala suggested the most plausible population loss to severe fire was 77% 1 week after fire and 63% after 10 years (with uncertainty increasing with time since fire), making the koala one of the most sensitive species to severe fire (Legge et al, 2022). Population response to mild fires was predicted to be about a 40% reduction after 1 year (Legge et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to centuries of ongoing degradation, in the 2019-2020 summer, Australia experienced the largest fire season on record (Boer et al 2020). These fires burned ∼104 000 km 2 of vegetation across southern Australia, with 545 flora (Gallagher et al 2021) and 114 fauna identified as immediate priorities for conservation action due to a substantial proportion of their habitat being impacted, their threat status, and their high sensitivity to fire (Legge et al 2022). Of the 114 priority fauna species, 90 (68 vertebrates and 22 invertebrates) were listed as threatened by IUCN, and/or national legislation (Legge 2022), driven mostly by habitat loss, fragmentation, and degradation .…”
Section: Introductionmentioning
confidence: 99%
“…These fires burned ∼104 000 km 2 of vegetation across southern Australia, with 545 flora (Gallagher et al 2021) and 114 fauna identified as immediate priorities for conservation action due to a substantial proportion of their habitat being impacted, their threat status, and their high sensitivity to fire (Legge et al 2022). Of the 114 priority fauna species, 90 (68 vertebrates and 22 invertebrates) were listed as threatened by IUCN, and/or national legislation (Legge 2022), driven mostly by habitat loss, fragmentation, and degradation . A multi-threat analysis is required to assess opportunities to address the many processes that degrade species habitat-which then helps to recover these priority species.…”
Section: Introductionmentioning
confidence: 99%